دراسة ميدانية للفوهات المطرية وتصريفها في مدينة اللاذقية - وزان, أحمد (Latakia University Journal -Engineering Sciences Series, 2019)
تتميز مدينة اللاذقية بوجود شوارع ثانوية أكثر من الشوارع الرئيسة. وتعاني من وجود شوارع ذات ميول كبيرة نظرا لأنها مدينة متنوعة التضاريس. وتكون الهطولات المطرية بنسبة واحدة تقريبا على كافة مناطقها كونها مدينة صغيرة. تم جمع المعلومات عن واقع التصريف المطري وتوزع الفوهات المطرية الموجودة لمجموعة من الشوارع والتي تعد محاور مرور أساسية في مدينة اللاذقية وهي: شارع 8 آذار,حلب, الجمهورية,عبد الرحمن الغافقي, القدس, المدينة المنورة وشارع طرابلس. نفذ هذا البحث ميدانيا بدراسة ميول الشوارع, والتباعد بين الفوهات المطرية فيها ونوع الفوهات وتوزعها وشكلها ثم تصنيف الفوهات من ناحية التصريف. تبين لنا نقاط الضعف في تصريف مياه الأمطار على مدار العام وفي بداية الخريف وبداية الربيع خاصة, وأن جميع الشوارع تعاني من مشاكل في التصريف بسب عدم قدرة الفوهات المطرية على إمرار الغزارة المصممة لأجلها وتوزعها العشوائي وعدم مراعاة الميول الطولية والعرضية للشوارع واتجاهاتها. تم اقتراح مجموعة من الإجراءات تؤمن عمل الفوهات بأفضل حالاتها, وإمكانية إضافة عدد منها, واعتماد شكل للتوضع حسب ميل الشوارع وفصل بعض القطاعات من الشوارع لتسهيل إمكانية التصريف, واعتماد الأقنية المطرية الطولية للميول الكبيرة على جانبي الطريق والاقنية المطرية العرضية عند بداية ونهاية الأنفاق, والصيانة الفصلية للمجارير والفوهات, وتحديد مواعيد الغسل الأساسية للفوهات. Lattakia city is characterized by the presence of more secondary streets than main ones. The city suffers from streets of multiple levels with different tendencies. Since it is a small city the amount of rainfall almost covers the whole city. Information about the reality of the distribution of rain nozzles and drainage was collected from seven main streets: March-8, Allepo, Republic, Abd Al-Rahman Al- Ghafiki, Al-Quds, AL-Madina AL-Monawara, and Tripoli. The tendency of the streets, spaces between rain nozzles, kinds and shape of nozzles and their distribution in the streets and classification of nozzles in terms of their rainfall disposal were studied. A weakness in rainfall disposal was found in the streets, generally and at the beginning of autumn and early spring especially. This is due to the random distribution of the nozzles, their inability to pass the abundance of the rain designed for it and non- observance of the longitudinal and spin-off slope of the streets. Many procedures were suggested to ensure the best work of nozzles and the possibility of adding some of them, to have a format and direction adapted to the slope of the streets, to separate some of street sectors to facilitate the possibility of discharge, and the adoption of longitudinal rain multichannel on both sides of the streets of big tendencies and rain channels – off at the beginning and end of tunnels, seasonal maintenance of the nozzles quarterly sewer and scheduling the main wash of the nozzles.